Kadar Nitrat Okside Pada Ibu Hamil Trimester III Dengan Hipertensi Gestasional - Juwita; Irfan Idris; Fatmawati Madya (Jurnal Bidan Cendrawasih Palu, 2020)
Nitric Oxcide is an essential amino acid L-arginine in vascular endothelial cells and mediates relaxation of smooth muscle which causes vaso contraception of capillary vessels, that causes increasing blood pressure and becoming hypertension. This study aims to determine whether the value of Nitric Oxcide levels in hypertension pregnant women is lower or higher than pregnant women without hypertension. The study was conducted at RSIA St. Fatimah Makassar, Jumpandang Baru Health Center and Antang Perumnas Health Center, with the research method using a purposive sampling technique in accordance with the inclusion criteria of trimigravida pregnant women, third trimester pregnant women, diagnosed with gestational hypertension based on the results of the examination and medical record, willing to be a respondent and sign an informed consent. The results showed that the Nitric Oxside level in gestasional hypertension pregnant women (13.31 ng/ml) was higher than the Nitric Oxcide level of pregnant women without gestational hypertension (11.88 ng/ml) and then Mann Whitney test was performed p = 0.787 ( p â‰¥ 0.05).